Production and 3D visualization of high-level data of minor bodies: The MATISSE tool in the framework of VESPA-Europlanet 2020 activity. Issue 8 (15th October 2018) - Longobardo, A.; Zinzi, A.; Capria, M.T.; Erard, S.; Giardino, M.; Ivanovski, S.; Fonte, S.; Palomba, E.; Di Persio, G.; Antonelli, L.A.
Abstract: The main goal of the VESPA (Virtual European Solar and Planetary Access) activity, developed in the framework of the EU-funded project Europlanet 2020 Research Infrastructure, is the application of Virtual Observatory standards to planetary data, in order to increase their sharing, visualization, interoperability and combination. The VESPA main search interface already uses some tools for analysis of planetary data, whereas other developed tools are going to be integrated on VESPA, e.g. MATISSE (Multi-purpose Advanced Tool for Instruments for the Solar System Exploration). This tool works on PDS data allowing analysis and 3D visualization of hyperspectral images. It is particularly suitable for minor bodies, where data projection on the shape model is fundamental to relate data to topographic and geological context. This paper shows the new functions implemented on the MATISSE tool for the study of minor bodies, aimed at the development of derived and high-level products, such as reflectance, photometrically corrected reflectance, absorption band descriptors and spectral ratios, and at their visualization on shape models. The developed products are commonly used to analyze hyperspectral data and hence a web based tool allowing their retrieval and visualization is important to hasten and support research activity on minor bodies.